IDENTIFIKASI BIDANG GELINCIR DENGAN METODE TAHANAN JENIS KONFIGURASI DIPOLE-DIPOLE DAERAH BAMBANKEREP NGALIYAN SEMARANG - Aliyatarrafiah Aliyatarrafiah; Agus Setyawan; Sugeng Widada (Youngster Physics Journal, 2014)
Shallow exploration of subsurface commonly use resistivity method which the electricity principles in the earth. The aims of this research are identify slip surface and slope safety factor at Pucung Bambankerep Ngaliyan Semarang using dipole-dipole configuration. The results of measurements are voltage and electric current to calculate the apparent resistivity value then processed by RES2DIV software for determine the lithology and the slip surface area. The value of slope safety factor was 1,332 from modelling by Rockscience software. The results present that lithology in the study area consist of clay, sand, sand gravel, and breccia. There is a slip surface at a depth of between 1,20 to 6,10 m.  Keywords: slip surface, Rockscience, resistivity, dipole-dipolee